Head Shape and the Characteristics of Female Pelvis. More about Brachycephalization - Budnik, Alicja; Jóźwiak, Mariola (Anthropological Review, 1985)
Looking for the mechanism of brachycephalization attention was focused on the connection between the size of female pelvis and the shape of her head. The size and shape of the small pelvis could have a connection with fertility. This problem was studied on bone material analysing traces of pregnancies and deliveries.